Diachronic analysis with the internet?: Will and shall in ARCHER and in a corpus of e-texts from the web - Nesselhauf, Nadja (Corpus linguistics and the web, 2007)
Abstract This paper investigates the potential of a quick-and-dirty corpus compiled from the web for diachronic analysis. The development of the future time expressions will, shall, and ‘ll in 19th century British English is first studied on the basis of a “traditional” diachronic corpus, ARCHER, and then on the basis of a corpus of fiction texts created from electronic texts available on the internet. In addition to the overall changes in the relative occurrences of the three forms, the changes in three types of linguistic contexts (person, negation, and if-clause environments) are investigated. One of the main differences found in the results based on these two (types of) corpora is the development of ‘ll: While the results from ARCHER point to a decrease in this expression in the 19th century (both in fiction texts and overall), the results from the fiction corpus point to an increase. Closer investigation reveals considerable inter-textual variation in the use of this form. The analysis demonstrates that, although not reliable as the only source for diachronic analysis, a quick-and-dirty corpus from the web can yield insights that can supplement those gained by a traditional corpus.